Strategy implementation style and public service effectiveness, efficiency, and equity - Rhys Andrews; Malcolm J. Beynon; Elif Genc (Administrative Sciences, 2017)
Strategic decision-making theories suggest that organizations that combine rational and incremental strategy implementation styles are likely to perform better than those that emphasize a single style. To assess whether these arguments apply to the public sector; we explore the strategy implementation style and perceived service effectiveness, efficiency and equity of Turkish municipal government departments. Using fuzzy cluster analysis, we identify four distinctive though inter-related styles of strategy implementation in our sample organizations: logical-incremental; mostly rational; mostly incremental; and no clear approach. A logical-incremental and mostly rational style of implementation are associated with better effectiveness, efficiency and equity; with the absence of an implementation style associated with worse performance. Theoretical and practical implications are discussed.
Keywords: 350; strategy; implementation; performance; public sector; quantitative analysis; fuzzy clustering